2016
DOI: 10.1016/j.joen.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Investigation of Matrix Metalloproteinases, Tissue Inhibitors of Matrix Metalloproteinases, and Matrix Metalloproteinase/Tissue Inhibitors of Matrix Metalloproteinase Complexes and Their Networks in Apical Periodontitis

Abstract: MMPs, TIMPs, and their complexes (MMP/TIMP) are involved in apical periodontitis by interacting with complex networks in the development of clinical features and the severity of bone destruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 39 publications
2
50
0
3
Order By: Relevance
“…()Dentsply–Mai.152 mm past WL602After Instrumenting14 daysELISAMartinho et al . ()Dentsply‐Mai.152 mm past WL601After InstrumentingELISASette‐Dias et al . ()2 mm past WL602After Instrumenting14 daysqPCRTRIzol (−µL)1025 at 12 000 g Zhi et al .…”
Section: Resultsmentioning
confidence: 99%
“…()Dentsply–Mai.152 mm past WL602After Instrumenting14 daysELISAMartinho et al . ()Dentsply‐Mai.152 mm past WL601After InstrumentingELISASette‐Dias et al . ()2 mm past WL602After Instrumenting14 daysqPCRTRIzol (−µL)1025 at 12 000 g Zhi et al .…”
Section: Resultsmentioning
confidence: 99%
“…), periapical interstitial fluid (Martinho et al . ), root canal exudate (Wahlgren et al . ) and gingival crevicular fluid (Baeza et al .…”
Section: Discussionmentioning
confidence: 99%
“…, Martinho et al . ). Previous studies have revealed that MMPs are involved in apical periodontitis in the development of clinical features by interacting with complex networks (Buzoglu et al .…”
Section: Introductionmentioning
confidence: 97%
“…, Martinho et al . ). Hence, the number of patients was set to be 30 per group, which is a sufficient number for a first tentative statistical analysis on continuous data (Krithikadatta ).…”
Section: Methodsmentioning
confidence: 97%